Dipole Antenna Radiation Pattern Optimization Using Parasitic Element Size and Location - Rajkumar Maniam; Thennarasa Sabapathy; Mohamed Nasrun Osman; Shanmuka Rooban Gunasekaran; Muzammil Jusoh (International Journal of Information System and Innovative Technology, 2025)
This work focuses on refining the radiation pattern of a dipole antenna by introducing a parasitic element and carefully adjusting its size and position. A dual‑band response emerges when the parasitic element is set to a width of 9 mm. The study explores dimensions of 0.98 Wh, 0.90 Wh, 0.70 Wh, and 0.75 Wh. For the first three cases, the element is placed 9.4 mm away from the dipole antenna. In the 0.75 Wh case, however, the spacing is increased to 11.8 mm, which produces a clear improvement in gain. These results show how subtle changes in geometry and placement can significantly influence antenna performance, offering a straightforward path to achieving dual‑band operation with enhanced radiation characteristics.